Life Satisfaction Among Filipino Older Adults Living in the Coastal Area - Rhona Marie Caingles Noquiao (Jurnal Keperawatan Indonesia, 2021)
Perhaps an all-encompassing aspiration of everyone who has ever walked the earth is to have lived his/her life to the fullest. However, the life experiences of each individual are the products of the decisions they make. This study aimed to investigate the relationship of older adults in Cabulijan, Tubigon, Bohol, Philippines’ self-esteem, social provisions received from other people, and relationships with other people to the level of their life satisfaction. Specifically, it sought to address the following queries: Is there a significant relationship between self-esteem, social provisions received from other people, and relationships with other people, and relationships with other people and the level of life satisfaction of older adults? Which of the factors of self-esteem, social provisions received from other people, and relationships with other people significantly contribute to the level of life satisfaction of older adults? Fifty respondents 65 years and older comprised the respondents of this research. The method used was cross-sectional explanatory design. Frequency, percentage, weighted mean, and Spearman’s rank correlation were the statistical tools applied in this study. The findings indicate support for the research hypotheses advanced in this study that posited the existence of a significant relationship between social provisions received from other people and relationships with other people, respectively, tended to manifest higher life satisfaction. This implies that the research respondents with higher ratings of each of the social provisions received from other people and relationships to other people tend to maintain higher life satisfaction whereas self-esteem has been found out to be of no significant relationship with life satisfaction. Abstrak Kepuasan Hidup Lansia Filipina yang Tinggal di Wilayah Pesisir. Kehidupan yang berkualitas merupakan dambaan semua orang. Namun, kesempatan tersebut tidak dapat dirasakan oleh semua orang karena pada hakikatnya, kehidupan yang berkualitas sangat bergantung pada pilihan hidup tiap individu. Penelitian ini bertujuan untuk mengidentifikasi hubungan antara self-esteem pada lansia di Cabuljan, Tubigol, Bohol, Filipina, dukungan, dan hubungan sosial terhadap tingkat kepuasan hidup pada lansia. Penelitian ini juga berfokus menjawab beberapa pertanyaan penelitian sebagai berikut: apakah terdapat hubungan yang bermakna antara self-esteem, dukungan sosial, dan hubungan sosial serta tingkat kepuasan hidup pada lansia? Manakah di antara faktor-faktor, seperti self-esteem, dukungan, dan hubungan sosial yang sangat berpengaruh terhadap tingkat kepuasan hidup pada lansia? Sebanyak 50 responden dengan rentang umur 65 tahun ke atas bersedia untuk menjadi responden pada penelitian ini. Metode yang digunakan ialah penelitian eksplanatori dengan desain cross-sectional. Kemudian, instrumen statistika penelitian yang digunakan ialah seperti frekuensi, persentase, rata-rata tertimbang, dan Spearman’s rank correlation. Pada penelitian ini ditemukan bahwa hasil penelitian mendukung hipotesa penelitian yang menyebutkan bahwa terdapat hubungan yang bermakna pada dukungan dan hubungan sosial dengan kepuasan hidup yang tinggi. Hal ini mengindikasikan bahwa para responden dengan dukungan dan hubungan sosial yang tinggi memiliki kepuasan hidup yang tinggi juga, namun ditemukan juga bahwa self-esteem tidak memengaruhi tingkat kepuasan hidup pada lansia. Kata Kunci: dukungan sosial, hubungan sosial, kepuasan hidup, lansia, self-esteem